Adverse events and contributing factors in Chinese nursing homes: a multisite cross-sectional study - Wang, Zhangan; Qi, Xiang; Shi, Ying; Shao, Lu; Li, Wei; Xie, Xiyan; Wu, Bei; Zhang, June (Frontiers in Public Health, 2025)
BackgroundAdverse events in nursing homes, which are unintended incidents causing unnecessary harm to older residents. Previous studies in Chinese populations often focused on adverse events in hospitals, rather than residents in nursing homes. Additionally, they tended to focus on single incident rather than multiple types of adverse events. This study aims to assess the occurrence and contributing factors of multiple adverse events perceived by staff in Chinese nursing homes.MethodsA cross-sectional survey was conducted among 691 frontline staff from 11 nursing homes in Southern China (August 2021–January 2022). Data were collected using a General Information Questionnaire, the Adverse Event Reporting Awareness Scale, and the Adverse Event Reporting Habit Scale. Logistic regression models were employed to analyze the contributing factors of adverse events.ResultsA total of 13 types of adverse events were screened out in nursing homes, and 477 (69.0%) participants reported that the adverse events “had happened” in the past year. The most common events were falls, unplanned extubation, and pressure sores. Clinical staff were 2.06 times more likely than frontline workers to report adverse events (95% CI = 1.13–3.76). Increased awareness (OR = 1.24, 95% CI = 1.15–1.34) and habitual reporting of adverse events (OR = 1.04, 95% CI = 1.01–1.08) were positively associated with higher reporting rates.ConclusionA significant proportion of staff reported adverse events, with clinical staff and those with better reporting habits noting higher occurrences. To enhance resident safety, nursing homes must prioritize preventing high-risk adverse events. Targeting frontline workers with lower reporting awareness and habits is crucial for effective interventions.